АКТУАЛЬНОЕ ЧЛЕНЕНИЕ ХУДОЖЕСТВЕННЫХ ТЕКСТОВ В ЯЗЫКОВОЙ КАРТИНЕ МИРА - Лариса Клокова; Ольга Клокова (Studia Rossica Posnaniensia)
The necessity of a multiaspect text analysis is caused by the characteristics of the text as an integral literary work. Actual articulation of textual units supposes taking into consideration the prior stipulation of the author’s choice with the regard for the structural and sensible text organization. Functional analysis and actual articulation are carried out by the example of artistic texts.